Comparison and Analysis of Important Product Standards and Technical Indicator Systems in the Papermaking Field-Taking Facial Tissue as An Example. Issue 1 (April 2021) - Li, Jing; Qiu, Wenlun; Yang, Lifei
Abstract: This article summarizes the current status of domestic and foreign standards for paper products and the standard system, compares and analyzes the domestic and international standards for facial tissue which is key product in the papermaking industry, combines the production technology, characteristics, and requirements of the product to establish key technologies index list for facial tissue, carries on comprehensive analysis of product standard index levels, testing methods, etc., and gives opinions and suggestions on product standard formulation and revision.